(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article forms an econometric model of the impact of factors affecting the value of capital of joint-stock companies. It also analyzes the factors affecting the capital value of joint-stock companies based on data from 2015 to 2020. In particular, the forecasts of multiplier coefficients, which are factors affecting the capital value of JSC " Kyzylkumtsement ", " Uzmetkombinat ", " Kokand Mechanical Plant" and "Quartz" from the joint-stock companies of the country. The existing problems were identified , then the forecast of the factors that influence the assessment of the capital value of the joint-stock company. That scientific proposal and practical recommendations were developed to address them.